1981
DOI: 10.1007/bf00552220
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sintered hydroxyapatite for prosthetic applications

Abstract: The compressive, flexural, torsional and dynamic torsional strengths of polycrystalline hydroxyapatite sintered at a temperature of 1300 ~ C for 3 h were found to be 509, 113, 76 and 68 MPa, respectively. The mechanical properties of polycrystalline hydroxyapatite are compared with those of cortical bone, dentine and enamel. SEM observation of the fracture surfaces indicates a predomination of transgranular failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 0 publications
3
124
1
3
Order By: Relevance
“…It should be noted that a wide range of values has been proposed in different studies: with the TC molecule values ranging from 0.35 to 12 GPa (Gautieri et al, 2011;Sun et al, 2002) and from 62.75 to 170 GPa for HA mineral (Weiner and Wagner, 1998;Cowin, 1989;Currey, 1969). The failure properties of TC molecules and mineral reported in literature (Akao et al, 1981;Shareef et al, 1993) are shown in Table 1.…”
Section: Mineralized Collagen Microfibrilmentioning
confidence: 94%
“…It should be noted that a wide range of values has been proposed in different studies: with the TC molecule values ranging from 0.35 to 12 GPa (Gautieri et al, 2011;Sun et al, 2002) and from 62.75 to 170 GPa for HA mineral (Weiner and Wagner, 1998;Cowin, 1989;Currey, 1969). The failure properties of TC molecules and mineral reported in literature (Akao et al, 1981;Shareef et al, 1993) are shown in Table 1.…”
Section: Mineralized Collagen Microfibrilmentioning
confidence: 94%
“…Synthetic, phase pure, dense, polycrystalline HA pellets (~1 cm in diameter) were prepared by an aqueous precipitation reaction between calcium hydroxide and phosphoric acid as described previously [5]. The pellets were found to be >98% of the theoretical density (3.13±0.015 g/cm 3 ), highly crystalline, phase pure, and approximately stoichiometric (Ca/P ratio=1.67) as measured by water displacement, wide angle X-ray diffraction, and X-ray fluorescence [6].…”
Section: Methodsmentioning
confidence: 99%
“…β = σ Akao et al [1981] and Shareef et al [1993], see [Fritsch et al, 2009] for further details, and they amount to 52.2 MPa and 80.3 MPa, respectively (see also Table 2). Beyond the elastic regime, we consider associated ideal plasticity according to Eq.…”
Section: Failure Properties Of Hydroxyapatite Crystals and Collagenmentioning
confidence: 99%